2021
DOI: 10.1177/0964528420971299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroacupuncture on the kisspeptin system in a pubertal rat model of polycystic ovary syndrome

Abstract: Objective: To explore the effects and mechanism of action of electroacupuncture (EA) in a rat model of pubertal polycystic ovary syndrome (PCOS). Methods: Female offspring of Sprague-Dawley rats receiving dihydrotestosterone (DHT) during pregnancy (days 16–19), as a model of prenatal androgenization, were divided randomly into three groups: model group (M), EA group, and sham acupuncture (SA) group (n = 8 each). A normal (N) group comprising female offspring of healthy pregnant rats not receiving DHT (n = 8) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…However, protein and mRNA expression of GHRL in the hypothalamus and ARC was decreased, and NPY mRNA levels was increased in the pubertal PCOS rats, indicating that NPY and GHRL in hypothalamus are involved in the occurrence of pubertal rats with PCOS. Although the specific mechanism is unclear, we speculate that NPY and GHRL in hypothalamus may participate in development of pubertal PCOS through kisspeptin / GnRH system in view of our previous study showed that the increased expression and release of kisspeptin and GnRH in hypothalamus are the key pathogenesis of pubertal PCOS [7]. The following provides evidence for our conjecture: a, Immunofluorescence doublelabeling experiment showed that GnRH neurons and kisspeptin neurons in ARC were the direct targets of NPY and GHRL in hypothalamus respectively, consistent with research of Conde et al [24] and Dhillon et al [25]; b, Kisspeptin, as the nodal regulatory centre of reproductive function, binds into kisspeptin receptor (G-protein coupled receptor-54, GPR-54) on GnRH neurons or NPY neurons and promotes GnRH and NPY secretion from hypothalamus [26][27][28][29]; c, Previous studies have shown that NPY is necessary for the pulsatility of GnRH release [30], promoting the secretion of GnRH [10].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, protein and mRNA expression of GHRL in the hypothalamus and ARC was decreased, and NPY mRNA levels was increased in the pubertal PCOS rats, indicating that NPY and GHRL in hypothalamus are involved in the occurrence of pubertal rats with PCOS. Although the specific mechanism is unclear, we speculate that NPY and GHRL in hypothalamus may participate in development of pubertal PCOS through kisspeptin / GnRH system in view of our previous study showed that the increased expression and release of kisspeptin and GnRH in hypothalamus are the key pathogenesis of pubertal PCOS [7]. The following provides evidence for our conjecture: a, Immunofluorescence doublelabeling experiment showed that GnRH neurons and kisspeptin neurons in ARC were the direct targets of NPY and GHRL in hypothalamus respectively, consistent with research of Conde et al [24] and Dhillon et al [25]; b, Kisspeptin, as the nodal regulatory centre of reproductive function, binds into kisspeptin receptor (G-protein coupled receptor-54, GPR-54) on GnRH neurons or NPY neurons and promotes GnRH and NPY secretion from hypothalamus [26][27][28][29]; c, Previous studies have shown that NPY is necessary for the pulsatility of GnRH release [30], promoting the secretion of GnRH [10].…”
Section: Discussionmentioning
confidence: 85%
“…Girls treated with GnRH analog drugs (GNRHa) have a significantly increased risk of PCOS during adolescence [6]. Pubertal rats with PCOS showed neuroendocrine dysfunction, characterized by hypersecretion of LH and kisspeptin and elevated release of GnRH from hypothalamus [7]. This elevated hypothalamic GnRH output is likely to stem in part from changed of the metabolic state of the body.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we have revealed that EA at sanyinjiao (SP6), zusanli (ST36), and qihai (CV6) all can improve the disturbed estrous cycles and ovarian polycystic morphological changes of PCOS rats [ 8 ] ( Table 1 , Fig 2 ). Therefore, the bilateral acupoints SP6, ST36 and CV6 were chosen in the EA group.…”
Section: Methodsmentioning
confidence: 99%
“…Acupoint location refers to “A new attempt of re-mapping acupoint atlas in the rat” by Xu et al [ 26 ]. The methods for EA and SA treatment refer to the previous research [ 8 ]. The details are as follows: Disposable, sterilized, stainless steel needles (Size: 0.16 x 25 mm; lot no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation